Assembling of MoS₂-based photosensitive organic-inorganic nanocomposites by exfoliation-restacking technique - Golub, A.S.; Lenenko, N.D.; Novikov, Yu.N.; Rumyantsev, B.M.; Bibikov, S.B.; Zhuravleva, T.S. (Functional Materials, 2006)
New nanocomposite compounds containing alternating layers of molybdenum disulfide and organic compound (dyes, polyvinyl alcohol) have been synthesized using sigle-layer dispersions obtained by exfoliation of bulk MoS₂ crystals. The formation mechanism of those compounds as weel as their structure are discussed. The data on photoelectric sensitivity of the system consisting of MoS₂-polyvinyl alcohol nanocomposite and some photoconductive polymers are reported.